Prolyl Oligopeptidase From Leishmania infantum: Biochemical Characterization and Involvement in Macrophage Infection - Lasse, Camila; Azevedo, Clênia S.; de Araújo, Carla N.; Motta, Flávia N.; Andrade, Milene A.; Rocha, Amanda Pereira; Sampaio, Iracyara; Charneau, Sébastien; Gèze, Marc; Grellier, Philippe; Santana, Jaime M.; Bastos, Izabela M. D. (Frontiers in Microbiology, 2020)
Leishmania infantum is a flagellated protozoan and one of the main causative agents of visceral leishmaniasis. This disease usually affects the human reticuloendothelial system, can cause death and available therapies may lead to serious side effects. Since it is a neglected tropical disease, the incentives for the development of new drugs are insufficient. It is important to know Leishmania virulence factors that contribute most to the disease in order to develop drugs. In the present work, we have produced L. infantum prolyl oligopeptidase (rPOPLi) in Escherichia coli, and investigated its biochemical properties as well as the effect of POP inhibitors on its enzymatic activity and on the inhibition of the macrophage infection by L. infantum. The optimal activity occurred at pH 7.5 and 37 oC in the presence of DTT, the latter increased rPOPLi catalytic efficiency 5-fold on the substrate N-Suc-Gly-Pro-Leu-Gly-Pro-AMC. The enzyme was inhibited by TPCK, TLCK and by two POP specific inhibitors, Z-Pro-prolinal (ZPP, IC50 4.2 nM) and S17092 (IC50 3.5 nM). Besides being a cytoplasmic enzyme, POPLi is also found in punctuate structures within the parasite cytoplasm or associated with the parasite plasma membrane in amastigotes and promastigotes, respectively. Interestingly, S17092 and ZPP prevented parasite invasion in murine macrophages, supporting the involvement of POPLi in the invasive process of L. infantum. These data suggest POPLi as a virulence factor that offers potential as a target for designing new antileishmanial drugs.